Long-term outcome of multilayer flow modulator in aortic aneurysms - Pintarić, Karlo (Radiology and oncology (Ljubljana), 2024)
ckground. This retrospective study investigated the efficacy of endovascular treatment with multilayer flow modu-lators (MFMs) for treating aortic aneurysms in high-risk patients unsuitable for conventional treatments.Patients and methods. Conducted from 2011 to 2019 at a single center, this retrospective observational study in-cluded 17 patients who underwent endovascular treatment with MFMs. These patients were selected based on theirunsuitability for traditional surgical or endovascular procedures. The study involved meticulous pre-procedural plan-ning, precise implantation of MFMs, and follow-up using CT angiography. The primary focus was on volumetric andflow volume changes in aneurysms, along with traditional diameter measurements. Moreover, the technical successand post-procedural complications were also registered.Results. The technical success rate was 100%, and 30-day procedural complication rate was 17.6%. Post-treatmentassessments revealed that 11 out of 17 patients showed a decrease in flow volume within the aneurysm sac, indicativeof a favorable hemodynamic response. The median decrease in flow volume was 12 ml, with a median relative de-crease of 8%. However, there was no consistent reduction in aneurysm size; most aneurysms demonstrated a medianincrease in volume for 46 ml and median increase in diameter for 18 mm.Conclusions. While MFMs offer a potential alternative for high-risk aortic aneurysm patients, their effectiveness in pre-venting aneurysm expansion is limited. The results suggest that MFMs can provide a stable hemodynamic environmentbut do not reliably reduce aneurysm size. This underscores the need for ongoing vigilance and long-term monitoringin patients treated with this technology
Keywords: anevrizma aorte; dolgoročno spremljanje; prostorninske meritve; večplastni modulator pretoka